C2 anatomy for translaminar screw placement based on computerized tomographic measurements - Kriangsak Saetia (2018)
© 2015 by Korean Society of Spine Surgery. Study Design: Anatomical study. Purpose: To evaluate the anatomy of the C2 lamina for translaminar screw placement based on computerized tomographic measurements. Overview of Literature: C2 translaminar screw insertion is a novel technique for atlanto-axial fixation. The risk of vertebral artery injury can be decreased by this technique. However, a large series of anatomical studies on C2 anatomy in Asian populations is still lacking. Methods: Two hundred adult C2 vertebrae were evaluated by computerized tomographic imaging. The measured parameters included inner and outer transverse diameters of C2 lamina, C2 laminar length and spino-laminar angle. C2 vertebrae with lamina screw placement feasibility were defined as those with inner transverse diameter larger than 3.5 mm. Results: The mean inner transverse diameter of the C2 lamina was 4.23±1.22 mm. It was significantly larger in males than in females (4.44±1.29 mm vs. 3.96±1.06 mm, p=0.005). The mean outer transverse diameter of C2 lamina was 6.64±1.36 mm. The mean C2 laminar length was 37.26±4.42 mm. The mean C2 spino-laminar angle was 56.42±6.42 degrees. Seventy-nine percents of patients had inner transverse diameter larger than 3.5 mm. Conclusions: C2 translaminar screw fixation was feasible in the majority of the adult population. However, there were some people who had small C2 lamina. We recommend preoperative computed tomography evaluation to confirm the feasibility of screw placement.